2024
DOI: 10.3389/fphar.2024.1298928
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the immunological interactions: targeting preeclampsia with Hydroxychloroquine’s biological mechanisms

Maja Gajić,
Bianca Schröder-Heurich,
Karoline Mayer-Pickel

Abstract: Preeclampsia (PE) is a complex pregnancy-related disorder characterized by hypertension, followed by organ dysfunction and uteroplacental abnormalities. It remains a major cause of maternal and neonatal morbidity and mortality worldwide. Although the pathophysiology of PE has not been fully elucidated, a two-stage model has been proposed. In this model, a poorly perfused placenta releases various factors into the maternal circulation during the first stage, including pro-inflammatory cytokines, anti-angiogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 237 publications
0
3
0
Order By: Relevance
“…Hydroxychloroquine, which demonstrates no adverse effects on the baby, has been employed with success. Furthermore, it has been observed that hydroxychloroquine carries a protective effect on endothelial function, although further assessment is warranted [4,[54][55][56][57].…”
Section: Treatment Options In Apsmentioning
confidence: 99%
“…Hydroxychloroquine, which demonstrates no adverse effects on the baby, has been employed with success. Furthermore, it has been observed that hydroxychloroquine carries a protective effect on endothelial function, although further assessment is warranted [4,[54][55][56][57].…”
Section: Treatment Options In Apsmentioning
confidence: 99%
“…The anti-inflammatory immune modulatory effects of HCQ 16,17 and casuistic reports of live births by women with previous RPL after HCQ-treatment 18,19 , have given rise to hypothesizes of several mechanisms for how HCQ can reduce the risk for PL in RPL 15 . HCQ is suspected to prevent systemic inflammation, oxidative stress, endothelial dysfunction, and hypercoagulability in pregnant women-states presumed associated with RPL 15 .…”
Section: Introductionmentioning
confidence: 99%
“…HCQ is suspected to prevent systemic inflammation, oxidative stress, endothelial dysfunction, and hypercoagulability in pregnant women-states presumed associated with RPL 15 . The potential immune mechanisms of HCQ in preventing RPL include I) inhibition of Toll like receptors (TRL) 15,17,20 , altering the T-cell activation and proliferation and consequently decreasing the levels of circulating TNF-α 15,21,22 , interferon-gamma 15,22 , and different interleukins 15,22 promoting the switch to a TH2 phenotype of a healthy pregnancy 15 , and II) by inhibiting platelet aggregation reducing the formation of blood clots 15 .…”
Section: Introductionmentioning
confidence: 99%